An Analysis Of The Potency And Opportunities For The Youth Participation In The Development Of Wiyono Village District Pesawaran Lampung - Juni Bayu Saputra; Banon Eko Susetyo (Kemudi, 2020)
This research is an exploratory study that wants to study the role of youth in village development in Wiyono Village, Gedong Tataan District, Pesawaran Regency. The research is based on the background of the fact that Wiyono Village is a City Village that has many facilities with relatively advanced population, but is still a developing village, not a fast developing village. This is interesting to study to find out what causes it. The research population was all village youths with 32 people drawn from eight hamlets in Wiyono Village. The study was conducted with an exploratory approach using qualitative descriptive methods. The results showed that the potential of Wiyono Village youth was in the high category with a score of 4, while the level of youth participation in village development was in a moderate position with a score of 3. The main cause of the lack of optimal youth participation was the lack of communication between the village government and the youth.